Art and Engagement in Early Postwar Japan - Jesty, Justin, 1974- (Book collections on Project MUSE., 2018)
"A cultural history of the relationship between art and politics in Japan, 1945-1960. Highlights the transformational nature of the early postwar period against the relative stasis, consolidation, and homogenization of the 1960s. Provides insight into the present by focusing on a period similarly characterized by decentralization and de-professionalization of culture and expansion of conceptions of what art is and who should be doing it"--